The Effect of Role Conflict, Role Ambiguity and Job Stress on Employee Performance - Purnomo, Kristanto Setio Hari; Lustono, Lustono; Tatik, Yuliana (Economic Education Analysis Journal, 2021)
This study aimed to determine the effect of role conflict, role ambiguity and job stress partially and simultaneously on performance. This research was a quantitative, and data used in this study were primary data with a questionnaire technique. The population in this research are all employees of Baperlitbang Banjarnegara regency, amounting to 51 people. The sampling technique in this research was saturated sampling technique. This study used data analysis in the form of multiple linear regression analysis with SPSS software. The results of this study indicated that role conflict partially had no effect on performance. Partial role ambiguity had a positive and significant effect on performance. Job stress had a negative and significant effect on performance. Meanwhile, role conflict, role ambiguity and job stress simultaneously had a positive effect on performance. Result the coefficient of determination in this study of 36.9% means that performance of Baperlitbang Banjarnegara employees was influenced by role conflict, role ambiuigity and job stress and the rest was influenced by other variables outside the study.